2019
DOI: 10.1093/ajcn/nqz111
|View full text |Cite
|
Sign up to set email alerts
|

Correcting for artifactual correlation between misreported month of birth and attained height-for-age reduces but does not eliminate measured vulnerability to season of birth in poorer countries

Abstract: Background Height-for-age z-scores (HAZ) are associated with month of birth (MOB) in many nutrition surveys, but that link could be an artifactual result of measurement error in child birthdates. Objective We corrected estimates of the associations between HAZ and MOB for a common type of age misreporting, to measure the remaining seasonality in HAZ and identify country characteristics associated with vulnerability to seasona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, while there was no seasonal pattern to sHCoV infection, birth in winter was significantly associated with sHCoV detection among cases and with the presence of LRTI among infants positive for sHCoV. Season of birth has previously been associated with poor birth outcomes [ 18 ] and nutritional indicators in children [ 19 , 20 ], which may be related to dietary or environmental factors [ 19 ]. Children born in autumn or winter have an increased risk of wheezing or asthma in later life, which may be partly mediated by respiratory tract infection [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, while there was no seasonal pattern to sHCoV infection, birth in winter was significantly associated with sHCoV detection among cases and with the presence of LRTI among infants positive for sHCoV. Season of birth has previously been associated with poor birth outcomes [ 18 ] and nutritional indicators in children [ 19 , 20 ], which may be related to dietary or environmental factors [ 19 ]. Children born in autumn or winter have an increased risk of wheezing or asthma in later life, which may be partly mediated by respiratory tract infection [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The specific kind of shock most often investigated is seasonal fluctuations in rainfall and temperature around the time of a child's birth, which is much more closely linked to attained height for children in poorer, more remote places than in towns and cities. Some of the apparent link between month of birth and height for age is due to random errors in recorded birth months among children without birth registrations (Larsen, Headey, and Masters 2019), but even after adjusting for those errors, there is significant variation in attained height by season of birth (Finaret and Masters 2019). Research to date has shown how sanitation, food markets, and local infrastructure can help households protect their children from seasonal climate fluctuations (Mulmi et al 2016;Shively 2017;Thapa and Shively 2018), leading to new work focusing on specific kinds of smoothing such as year-round access to a nutritious diet (Bai, Naumova, and Masters 2019).…”
Section: Agriculture Rural Livelihoods and Nutritionmentioning
confidence: 99%
“…The specific kind of shock most often investigated are seasonal fluctuations in rainfall and temperature around the time of a child's birth, which is much more closely linked to attained height for children in poorer, more remote places than in towns and cities. Some of the apparent link between month of birth and height for age is due to random errors in recorded birth months among children without birth registrations (Larsen, et al, 2019), but even after adjusting for those errors there is significant variation in attained height by season of birth (Finaret and Masters, 2019). Research to date has shown how sanitation, food markets and local infrastructure can help households protect their children from seasonal climate fluctuations (Mulmi, et al, 2016, Shively, 2017, Thapa and Shively, 2018, leading to new work focusing on specific kinds of smoothing such as year-round access to a nutritious diet (Headey, et al (2017d), (bai, et al, 2019).…”
Section: Rural Poverty and Limited Access To Infrastructure And Servicesmentioning
confidence: 99%